Problem-based learning analysis in strengthening college students’ interpersonal communication skill - Ndiung, Sabina; Menggo, Sebastianus (Intelektual Pustaka Media Utama, 2024)
This study seeks to analyse the incorporation of problem-based learning (PBL) in strengthening students' interpersonal communication skills, as well as the level of proficiency of students' interpersonal communication skills and the obstacles they face in acquiring them. This study was a crosssectional survey conducted in May 2023 with 315 college students enrolled in six English Study Programs at six universities in three Indonesian provinces. The questionnaires and interviews were used for recording data, which was then analysed using Jeffreys's amazing statistics program (JASP). Based on the data collected, it can be shown that the interpersonal communication profiles of 315 participants can be classified as falling within the medium category (average score=3.26). The primary challenge encountered by participants in developing their interpersonal communication skills is attributed to difficulties arising from the accent of their conversation partner, as indicated by a mean score of 4.6. The result mandates that educators provide an appropriate and effective learning method. PBL is an effective alternative as its principles, syntax, implementation stages, orientation, and benefits are capable of helping students overcome interpersonal communication challenges. PBL model is intended to provide students with the skills needed for problem-solving, increasing logical thinking, collaboration, and communication.